DAYA SAING KOMODITAS PERTANIAN UNGGULAN INDONESIA: PERBANDINGAN DENGAN NEGARA LAIN DI ASEAN DAN POTENSINYA - Abyan Rai; Ahmad Faisal (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
Abundant natural resources become a great potential for the Indonesian agricultural sector if they are managed properly. A large contribution from the agricultural sector is highly dependent on its superior commodities. However, liberal international trade creates a real challenge for leading commodities in the agricultural sector to have high competitiveness, at least in the ASEAN region. This study aims to analyze the export competitiveness of Indonesia's leading agricultural sector commodities and analyze the potential for improvement. The commodities analyzed were coffee, pepper, palm oil, tea, and tobacco. The data used is data on export conditions in 2019. The analysis is carried out using Revealed Comparative Advantage (RCA), Revealed Comparative Trade Advantage (RCTA), and Porter's diamond. The results of the analysis show that Indonesia's leading commodities have competitiveness in the global market and rank at the top in ASEAN based on RCA. RCTA shows that Indonesia's tea and tobacco commodities are not yet competitive in the global market. Porter's diamond shows that the competitiveness of Indonesia's leading agricultural commodities has the potential to be developed.